Pelatihan Pengelolaan Perpajakan di Bumdes Sambeng Lamongan - Sri Yaumi; Qosim Qosim; Ayu Wigati; Rina Febrianti Miftahur Rohmah (BADAN PENERBIT STIEPARI PRESS, 2021)
In order to implement the Tri Dharma of Higher Education, the Institut Teknologi dan Bisnis Ahmad Dahlan Lamongan community service team conducted tax management training for treasurers and financial managers at Bumdes Sambeng Lamongan. The method of implementation with socialization and training, aims to provide understanding to Bumdes Sambeng regarding tax management. This community service activity was carried out for 4 months between May and August 2021 in the Sambeng village hall building. Presentation of taxation material is carried out systematically by prioritizing presentations, discussions and questions and answers. Every problem encountered in the context of tax management becomes material for discussion between the presenters (trainees) and the participants. Furthermore, continuous training is carried out dynamically where participants consult on each of the problems encountered in the implementation of the village-owned tax, consulting in the form of face-to-face meetings, or using communication devices such as telephones. The result of this activity is that treasurers and financial managers have a good understanding of tax management. This is evidenced by the good management of taxes at Bumdes Sambeng Lamongan.